The Effect of Dialysate Bicarbonate Concentration or Oral Bicarbonate Supplementation on Outcomes in Patients on Maintenance Dialysis: A Systematic Review and Meta-Analysis - Ashlee M. Azizudin; Samuel A. Silver; Amit X. Garg; Zoe K. Friedman; Andrea C. Cowan; Catherine M. Clase; Amber O. Molnar (Canadian Journal of Kidney Health and Disease, 2025)
Background: Metabolic acidosis is a common complication of kidney failure that is treated with bicarbonate supplementation. The addition of bicarbonate to the dialysis solution and oral bicarbonate supplementation are used to treat metabolic acidosis in patients receiving dialysis, but the treatment approach that is best for patient health remains unknown. Objective: The purpose of this study was to determine whether the concentration of dialysate bicarbonate or the use of oral bicarbonate supplementation alters the risk of mortality, hospitalizations, cardiovascular and nutritional outcomes, and laboratory measurements in patients treated with maintenance dialysis. Design: Systematic review and meta-analysis. Setting: Any country of origin. Patients: Adult patients (≥18 years) receiving maintenance dialysis. Measurements: Extracted data included demographic characteristics and outcomes such as mortality, hospitalizations, cardiovascular events, surrogate markers of nutrition, and pre-dialysis and post-dialysis levels of serum bicarbonate, pH, calcium, potassium, and parathyroid hormone. Methods: We searched MEDLINE, Embase, CENTRAL, and Google Scholar through October 7, 2024 for studies examining dialysate bicarbonate concentration and/or oral bicarbonate supplementation in adults undergoing maintenance dialysis. Meta-analysis was performed for pre-dialysis serum bicarbonate and for pre-dialysis and post-dialysis calcium and potassium. Results: We identified 37 studies (n = 24,782 patients) with patients treated with hemodialysis (13 randomized trials, 10 non-randomized interventional studies, 14 observational studies) and 4 studies (n = 347 patients) with patients receiving peritoneal dialysis (3 randomized trials, 1 non-randomized interventional study). No randomized trials reported mortality or hospitalizations in hemodialysis patients. Studies reporting cardiovascular outcomes (n = 20) were small with inconsistent results. Most studies reporting nutritional outcomes (n = 21) reported no significant differences with dialysate bicarbonate concentration or oral bicarbonate supplementation but were small in sample size (largest study n = 200). Meta-analysis of parallel-group randomized trials comparing dialysate bicarbonate >35 mmol/L with ≤35 mmol/L found a mean difference of 3.5 mmol/L (95% confidence interval [CI] −0.6 to 7.7) in pre-dialysis serum bicarbonate. Limitations: Non-English and gray literature were excluded. Most studies were small or observational in nature, and heterogeneity further limited the ability to perform meta-analysis of outcomes such as mortality, hospitalizations, and cardiovascular outcomes. Conclusions: The evidence for the effect of higher vs lower dialysate bicarbonate concentration and oral bicarbonate supplementation on clinical outcomes in dialysis patients is very uncertain. There is a need for large, high-quality randomized controlled trials in this area.